ANALISIS KARAKTER DAN PERILAKU WIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM INSTITUT AGAMA ISLAM NEGERI PADANGSIDIMPUAN - Utari Evy Cahyani (KOLEGIAL, 2017)
Students at the Islamic Business and Economy Faculty has the potential to become an entrepreneur indicated by the participation level of students in various extracurricular activities the field of entrepreneurship. Increasing Islamic Business and Economy Faculty student participation in the entrepreneurship program is an indication that there is a change in the behavior of entrepreneurial students. Therefore, the purposes of this research are to analyze characteristics and behavioral factors of entrepreneurs Islamic Business and Economy Faculty student. The study was conducted in Islamic Business and Economy Faculty on September-October, 2017. The analysis used in this study, namely descriptive statistics and cross tabulation analysis. Results showed that most students have entrepreneurial behavior is high, the level of entrepreneurial knowledge is high, being entrepreneurial attitude and entrepreneurial action is high.